An ATP synthase harboring an atypical γ–subunit is involved in ATP synthesis in tomato fruit chromoplasts. (18th February 2013) - Pateraki, Irini; Renato, Marta; Azcón‐Bieto, Joaquín; Boronat, Albert
Summary Chromoplasts are non‐photosynthetic plastids specialized in the synthesis and accumulation of carotenoids. During fruit ripening, chloroplasts differentiate into photosynthetically inactive chromoplasts in a process characterized by the degradation of the thylakoid membranes, and by the active synthesis and accumulation of carotenoids. This transition renders chromoplasts unable to photochemically synthesize ATP, and therefore these organelles need to obtain the ATP required for anabolic processes through alternative sources. It is widely accepted that the ATP used for biosynthetic processes in non‐photosynthetic plastids is imported from the cytosol or is obtained through glycolysis. In this work, however, we show that isolated tomato (Solanum lycopersicum) fruit chromoplasts are able to synthesize ATP de novo through a respiratory pathway using NADPH as an electron donor. We also report the involvement of a plastidial ATP synthase harboring an atypical γ–subunit induced during ripening, which lacks the regulatory dithiol domain present in plant and algae chloroplast γ–subunits. Silencing of this atypical γ–subunit during fruit ripening impairs the capacity of isolated chromoplast to synthesize ATP de novo. We propose that the replacement of the γ–subunit present in tomato leaf and green fruit chloroplasts by the atypical γ–subunit lacking the dithiol domain during fruit ripening reflects evolutionary changes, which allow the operation of chromoplast ATP synthase under the particular physiological conditions found in this organelle.